Smurf1 aggravates non‐alcoholic fatty liver disease by stabilizing SREBP‐1c in an E3 activity‐independent manner. Issue 6 (17th April 2020) - Zhang, Xin; Zhan, Yutao; Lin, Wenjun; Zhao, Fei; Guo, Chaojing; Chen, Yujiao; Du, Mengge; Li, Dongnian; Zhang, Lingqiang; An, Wei; Wang, Hong‐Rui; Xie, Ping
Abstract: Non‐alcoholic fatty liver disease (NAFLD) is one of the most common liver disorders which are characterized by the accumulation of excessive lipid in hepatocytes. The precise pathogenesis of NAFLD is very complicated and remains largely unknown. Smad ubiquitination regulatory factor 1 (Smurf1) is crucial for numerous processes including bone homeostasis, embryogenesis, and pathogenic autophagy. In this study, we found that liver steatosis was alleviated in Smurf1 ‐deficient mice fed with high‐fat diet (HFD) for 19 weeks. The deletion of Smurf1 reduced the accumulation of lipid droplets and triglycerides in hepatocytes. The stability of sterol regulatory element‐binding protein‐1c (SREBP‐1c), a key transcription factor that mediates de novo lipogenesis, was markedly reduced in Smurf1 ‐deficient mice. The mechanistic study showed that Smurf1 interacts with SREBP‐1c and protects SREBP‐1c from ubiquitination and degradation by preventing the binding of SREBP‐1c to its ubiquitin E3 ligase Fbw7a. Thus, our study presented an E3 ligase catalytic activity‐independent function of Smurf1 in the fatty liver development.